Mitochondrial HMG-CoA Synthase Deficiency: A Cyclic Vomiting Mimic Without Reliable Biochemical Markers - Annie D. Niehaus MD; Holly Cooper MD; Chung U. Lee MD (SAGE Publishing, 2024)
Here, we report an individual, eventually diagnosed with HMG-CoA synthase deficiency, who presented with a cyclic vomiting phenotype. HMG-CoA synthase deficiency is a rare disorder affecting ketone body synthesis in which affected individuals typically present at a young age with hypoketotic hypoglycemia, lethargy, encephalopathy, and hepatomegaly, usually triggered by catabolism (e.g., infection or prolonged fasting). This individual presented with recurrent episodes of vomiting and lethargy, often associated with hypoglycemia or hyperglycemia, at 3 years of age. Metabolic labs revealed nonspecific abnormalities in her urine organic acids (showing mild elevation of dicarboxylic acids with relatively low excretion of ketones) and a normal acylcarnitine profile. Given her clinical presentation, as well as a normal upper gastrointestinal series, esophagogastroduodenoscopy with biopsies, and abdominal ultrasound, she was diagnosed with cyclic vomiting syndrome at 3 years of age. Molecular testing completed at 7 years of age revealed a previously reported pathogenic sequence variant (c.1016+1G>A) and a novel likely pathogenic deletion (1.57 kB deletion, including exon 1) within HMGCS2 consistent with HMG-CoA synthase deficiency. This individual's presentation, mimicking cyclic vomiting syndrome, widens the clinical spectrum of HMG-CoA synthase deficiency. In addition, this case highlights the importance of molecular genetic testing in such presentations, as this rare disorder lacks specific metabolic markers.